Pengembangan Multimedia Interaktif Berbasis Problem Based Learning Efektif dalam Meningkatkan Hasil Belajar Peserta Didik pada Materi Virus - Farah Alichia; Destien Atmi Arisandy; Mareta Widiya (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop interactive multimedia based on problem-based learning (PBL) on viruses to improve the learning outcomes of tenth-grade students at SMA Negeri 2 Lubuklinggau. This study employed a research and development (R&D) method using the ADDIE model. The results showed that the developed product was valid, with an average validity score of 4.72, and the practicality assessment sheet analysis by teachers and students met the practical criteria with an average percentage of 91.22%. The effectiveness assessment obtained an average n-gain score of 0.75, classified as high. Based on the results, it can be concluded that interactive multimedia based on problem-based learning has proven valid, practical, and effective in improving learning outcomes in biology learning for tenth-grade students at SMA Negeri 2 Lubuklinggau.   Keywords: ADDIE, Interactive Multimedia, Problem-Based Learning.